2018
DOI: 10.1016/j.jradnu.2018.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Radiation Exposure From Computed Tomography of the Head

Abstract: In an effort to reduce radiation exposure from computed tomography (CT), practitioners and facilities need to monitor radiation exposure while delivering high-quality diagnostic exams. Computed tomography scanners have a range of pre-programmed protocols for different examination types, with set values for tube potential, tube current, and rotation time (American Association of Physicists in Medicine, 2007). One way to minimize a patient's exposure to radiation from CT is the use of an automatic exposure contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Studies have reported about 1.5 -2% of cancer cases may be caused by higher doses of radiation currently used in CT (Abdulqadir et al, 2016). The Radiological Society of North America (RSNA) in 2012 stated that average radiation dose from abdominal CT examinations is about 10mSv while that for brain is just about 2mSv (Vega, 2014). Radiation dose of 10mSv and above carry higher risks of radiation induced injuries.…”
Section: Assessment Of Average Radiation Dose For Abdominal Computed mentioning
confidence: 99%
“…Studies have reported about 1.5 -2% of cancer cases may be caused by higher doses of radiation currently used in CT (Abdulqadir et al, 2016). The Radiological Society of North America (RSNA) in 2012 stated that average radiation dose from abdominal CT examinations is about 10mSv while that for brain is just about 2mSv (Vega, 2014). Radiation dose of 10mSv and above carry higher risks of radiation induced injuries.…”
Section: Assessment Of Average Radiation Dose For Abdominal Computed mentioning
confidence: 99%